2013
DOI: 10.1177/0194599813505078
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge Complications Predict Reoperation and Mortality after Otolaryngologic Surgery

Abstract: This is the first study of overall postdischarge events after otolaryngologic surgery. PDC rates in otolaryngology occur soon after discharge, are procedure specific, and are associated with reoperation and mortality. Targeted procedure-specific triage and follow-up plans for high-risk patients may improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 22 publications
1
51
1
Order By: Relevance
“…Chen et al investigated 48 028 adult patients undergoing in-patient otolaryngologic surgery. They found that patients who had a postdischarge complication were nine times more likely to have an unplanned reoperation or die than those who did not have a postdischarge complication [34]. In this study, HNC patients typically had the highest rate of postdischarge complications.…”
Section: Surgerymentioning
confidence: 53%
“…Chen et al investigated 48 028 adult patients undergoing in-patient otolaryngologic surgery. They found that patients who had a postdischarge complication were nine times more likely to have an unplanned reoperation or die than those who did not have a postdischarge complication [34]. In this study, HNC patients typically had the highest rate of postdischarge complications.…”
Section: Surgerymentioning
confidence: 53%
“…7 For inpatient otolaryngologic surgery, the most common postdischarge complications were surgical site infections, other infections, and deep venous thrombosis. 8 In the present analysis using ACS-NSQIP-P, we identified that the most common 30-day adverse event rates were for return to the operating room, surgical site infections, pneumonia, sepsis, and reintubation (Table 3). The disparity between adult and pediatric outcomes demonstrates the need for pediatric-focused investigations to identify specific and actionable improvement opportunities.…”
Section: Discussionmentioning
confidence: 80%
“…The varying size and acuity of patient care in participating institutions is useful to more globally describe patient characteristics and procedures associated with adverse 30‐day postoperative outcomes. To our knowledge, no studies have utilized the ACS‐NSQIP‐P PUF to assess specific outcomes in pediatric airway reconstructive surgery, although there have been studies performed using the adult NSQIP database to assess adult and pediatric otolaryngic procedures …”
Section: Discussionmentioning
confidence: 99%